Particle swarm optimization aplicada ao planejamento da expansão de sistemas de transmissão - Resende, Adriana Souza [UNESP] (2014)
In this work, two methodologies to solve the transmission network expansion planning (TNEP) problem have been proposed. The first one is a presentation of a meta-heuristic based algorithm, Particle Swarm Optimization (PSO), as a tool to solve static TNEP problems. In this proposition, the mathematical models of transportation model and the DC model have been used. Both the models have been implemented via the programming language of FORTRAN and the commercial solver of MINOS has been used to solve the related LP problems. The second proposal, presents the TNEP problem considering multiple generation scenarios using the disjunctive linear model. This model has been implemented via AMPL and solved by the commercial solver of CPLEX. In order to validate and qualify the first proposed methodology, five case studies have been carried out, these cases are: Garver, IEEE 24-bus, Southern Brazil, Colombian, and Brazilian North-Northeast systems. And for the second proposed methodology, 3 case studies have been used such as: Garver, IEEE 24-bus and Southern Brazil test systems. The results show the effectiveness and the usefulness of the proposed methodologies